TEKNIK JIGSAW CUTTING PADA OUTERWEAR - Zahra, Lutfia; Nabilah, Nabilah (Practice of Fashion and Textile Education Journal, 2022)
This study aims to obtain an assessment of the feasibility of the jigsaw cutting technique on outerwear. The assessment in this study was carried out by 5 expert panelists who were assessed based on aspects of appearance, fit and sustainability.The research methodology used is experimental with a quantitative approach, the design model used is Pre-Experimental Design with One-Shot Case Study design. The data collection technique used a questionnaire with Rating Scale. The application of the jigsaw cutting technique on outerwear is assessed based on the criteria of zero waste clothing, namely meeting the visual appearance, fit, and sustainability aspects to obtain good results. The results of the assessment state that the sustainability aspect is considered the most dominant aspect. This is because the sustainability aspect is the most important aspect that must be considered in the manufacture of products that apply the concept of zero waste. While the appearance aspect gets the lowest results because the color combination (blue-beige) that is applied does not pay attention to the combination of tin, tone and shade. The results of the study prove that the application of the jigsaw cutting technique can be an alternative in manufacture of outerwear.